A New Type Surfactant for Enhanced Oil Recovery - LIANG, CHENGHAO; ZHANG, ZHIJUN (Asian Journal of Chemistry, 2010)
A new surfactant namely 2-p-alkylbenzoyl-1-carboxyethane sulfonates (ABCES) has been synthesized by Friedel-Crafts acetylation and sulfonation reaction using surfural extracted petroleum fraction. The presence of sulfo and carboxyl groups in the synthesized compound was identified by IR analysis. The critical micellar concentration (CMC) and minimum surface tension of ABCES at 20 ºC is 1.76 mg/L and 36.18 mN/m, respectively. The surfactant was superior to petroleum sulfonate (PS) which is prepared with petroleum fraction. Ultralow interfacial tension were obtained by 0.3 % ABCES solution in a 0.6-1.2 % Na2CO3 solution and were maintained at 0.3 % ABCES + 1.2 % Na2CO3 solution with Ca2+ + Mg2+ concentration ≤ 600 mg/L while for PS Ca2+ + Mg2+ concentration ≤ 300 mg/L. ABCES was acted as a low cost, highly tolerant to Ca2+ + Mg2+ surfactant for enhanced oil recovery.